An Examination of Differences Between Organizational Legitimacy and Organizational Reputation* - Deephouse, David L.; Carter, Suzanne M. (Journal of Management Studies, 2005)
abstract Organizational legitimacy and organizational reputation have similar antecedents, social construction processes and consequences. Nonetheless, an improved understanding of relationships between legitimacy and reputation requires that differences between the two be specified and clarified. Our examination of past research indicates that legitimacy emphasizes the social acceptance resulting from adherence to social norms and expectations whereas reputation emphasizes comparisons among organizations. We empirically examine two antecedents of the financial, regulatory, and public dimensions of legitimacy and reputation in a population of US commercial banks. We find that isomorphism improves legitimacy, but its effects on reputation depend on the bank's reputation. Moreover, higher financial performance increases reputation, but does not increase the legitimacy of high performing banks.